ANALISIS TINGKAT PENDAPATAN UMKM PADA OBJEK WISATA RUMAH SENI DOLOK SIPIAK KABUPATEN SIMALUNGUN - ayu, ade rahma; fuji yanti fadlillah (Jurnal Manajemen dan Pemasaran, 2023)
This study aims to determine the income of MSME;s seen from the aspect of capital, length of business, business location and working hours at the Dolok Sipiak Art House Tourism Object, Simalungun Regency and the constraints of MSME’s in increasing income. This research approach is a qualitative approach and descriptive research type. Respondents to the research were 4 (four) in the Dolok Sipiak Art House Tourism Object area, Simalungun Regency. Data collection was carried out using interview techniques, observation and literature studies. The results showed that the income of MSME’s in the Dolok Sipiak Art House Tourism Object area, Simalungun Regency, it was found that the income of MSMEs Souvenirs was Rp.400,000/day with the lowest income Rp.300,000/day, UMKM Coffee Shops had the highest income Rp. 300,000/day and the lowest is Rp. 250,000/day. For other Coffee Shop SME’s with a smaller business scale compared to the existing Coffee Shop, the highest income is Rp. 200,000/day and the lowest is Rp. 150,000/day. The obstacles faced by MSME’s in the Dolok Sipiak Art House Tourism Object area, Simalungun Regency in increasing their income are the reduced number of visitors, decreased consumer purchasing power, limited business capital and locations/buildings where the business is not permanent.